Ecocement for beach erosion control - Chua, Xue Ning (Nanyang Technological University, 2022)
Beach erosion happens when there is a net loss of sand at beaches and at coastlines. Such erosion has been accelerating in recent years due to sea level rise and human activities. Current solutions to overcome beach erosion includes hard and soft solutions. Hard solutions have negative effects on the environment while soft solutions mainly work well as temporary measures. Therefore, a new approach, Ecocement, was proposed and investigated in this project. Experimental studies were carried out to test the feasibility and effectiveness of using Ecocement on beach sand to control beach erosion. Ecocement is the product of a bio-cementation process. It is based on the microbially induced carbonate precipitation (MICP) process which uses microbes to catalyse biochemical reactions to produce calcium carbonate precipitates as binding agent for sand particles. In this project, soybean was used as an alternative to produce catalyst enzymes for the enzyme induced carbonate precipitation (EICP) process. Besides eliminating biosafety concern, soybean enzyme is cost-effective to be used for Ecocement. It also reduces carbon footprint by using sustainable raw materials and simplified extraction methods. Laboratory tests and on-site tests were carried out to assess the mechanical properties of the treated beach sand. Unconfined compression (UC) tests were used to measure the shear strength of the treated sand in laboratory. Penetration tests using a pocket penetrometer were used to test the strength of the treated sand slope on-site. The effectiveness of Ecocement treatment was also represented through the measurement of cumulative calcium consumption and final calcium carbonate content. The experiment results had shown that EICP is feasible in cementation of the beach sand, thus reducing sediment transportation, and controlling erosion.